Improvements in SOD mimic AEOL-10150, a potent broad-spectrum antioxidant - Xiao-rui Zhang (Military Medical Research, 2018)
Abstract AEOL-10150 is a broad-spectrum metalloporphyrin superoxidase dismutase (SOD) mimic specifically designed to neutralize reactive oxygen and nitrogen species. Research has shown that AEOL-10150 is a potent medical countermeasure against national security threats including sulfur mustard (SM), nerve agent exposure and radiation pneumonitis following a radiological/nuclear incident sufficient to cause acute radiation syndrome (ARS). AEOL-10150 performed well in animal safety studies, and two completed phase 1 safety studies in patients demonstrated that the drug was safe and well tolerated, indicating that AEOL-10150 has potential as a new catalytic antioxidant drug. In this article, we review improvements in AEOL-10150 in preclinical pharmacodynamic studies, especially regarding anti-SM, chlorine gas and radiation exposure studies.